Canadian Asthma Consensus Conference Summary of Recommendations - Pierre Ernst; J Mark Fitzgerald; Sheldon Spier (Canadian Respiratory Journal)
The Asthma Committee of the Canadian Thoracic Society invited a group of Canadian physicians with a particular interest in asthma to meet in Montebello, Quebec, March 9-12, 1995 to arrive at a consensus statement on the optimal approach to the management of asthma in the pediatric and adult ambulatory care settings. The societies and associations represented are listed in the appendix with the names of the contributors to this document. The objectives of the Montebello conference were: 1. To review the current ambulatory care management of asthma in Canada; 2. To develop guidelines with the participation of family physicians and specialists; 3. To develop guidelines which are evidence-based; 4. In creating evidence-based guidelines to focus attention on aspects of asthma management that are currently not supported by randomized controlled trials; 5. To develop strategies that allow for the implementation of rational guidelines at a local level. Recommendations were based on a critical review of the scientific literature by small groups prior to the meeting and are categorized according to the strength of the scientific evidence supporting each recommendation (Table 1).